Bone mineral density in Australian children, adolescents and adults with cystic fibrosis: a controlled cross sectional study. Issue 2 (3rd February 2004) - Buntain, H M; Greer, R M; Schluter, P J; Wong, J C H; Batch, J A; Potter, J M; Lewindon, P J; Powell, E; Wainwright, C E; Bell, S C
Abstract : Background: Low bone mineral density (BMD) is recognised in individuals with cystic fibrosis (CF) although the pathogenesis remains unclear. The aims of this study were to compare BMD over a broad continuum of Australian individuals with CF with healthy controls and to examine the relationship between BMD and clinical parameters including physical activity, nutrition, and vitamin D levels. Methods: BMD of the lumbar spine (LS), total body (TB), femoral neck (FN), cortical wrist (R33%), and distal wrist (RUD) was examined in 153 individuals with CF aged 5.3–55.8 years (84 males) and in 149 local controls aged 5.6–48.3 years (66 males) using dual energy x ray absorptiometry. Anthropometric variables, body cell mass, markers of disease severity, corticosteroid usage, measures of physical activity, dietary calcium and caloric intake and serum vitamin D were assessed and related to BMD. Results: Compared with controls, mean BMD was not significantly different in children aged 5–10 years with CF. Adolescents (females 11–18 years, males 11–20 years) had reduced TB and R33% BMD when adjusted for age, sex, and height (difference in BMD (g/cm 2 ) adjusted means between control and CF: TB = 0.04 (95% CI 0.01 to 0.07); R33% = 0.03 (95% CI 0.01 to 0.06)). BMD was reduced at all sites except R33% in adults (difference in BMD (g/cm 2 ) adjusted means between control and CF: TB = 0.05 (95% CI 0.02 to 0.09); LS = 0.08 (95% CI 0.03 to 0.14); FN = 0.09 (95% CI 0.03 to 0.15); RUD = 0.03 (95% CI 0.01 to 0.05)). In children/adolescents BMD was weakly associated with nutritional status and disease severity. Conclusions: BMD was normal in a well nourished group of prepubertal children with CF. A BMD deficit appears to evolve during adolescence and becomes more marked in adults. Individuals with CF should optimise nutrition, partake in physical activity, and maximise lung health in order to optimise BMD. Further longitudinal studies are required to understand the evolution of reduced BMD in young people and adults with CF.